The human blink reflex - Shahani, Bhagwan (1970)
A detailed study of the human blink reflex in the different parts of the orbicularis oculi muscle has been carried out. The first component of the blink reflex has been demonstrated in patients with Friedreich's ataxia, who have selective loss of large sensory fibres resulting in loss of proprioceptive input. It has been established that both components of the blink reflex are cutaneous reflexes which represent a highly organized and purposeful mechanism in man. Afferent fibres for the blink reflex have been identified in the human supraorbital nerve and their conduction velocity has been estimated for the first time in man. It has been demonstrated that both components of the blink reflex are mediated by the same group of afferent fibres.